Answer:
53/6 = 8.83
Step-by-step explanation:
2 x -7 = -14
-62 / 12 = -5.16667
-5.16667 - (-14) = 8.83333
Final answer: 8.83
I hope this helps you! :D
the answer 11
Step-by-step explanation:
6+16=22
22÷2=11
Answer:
raise a product to a power.
you first simplify the parenthesis in the numerator by raising 2 by the power of three and multiplying the exponents.
i suck at explaining, but after the first step the expression looks like:
![(\frac{8r^{6}t^{3} }{4t^{2} })^{2}](https://tex.z-dn.net/?f=%28%5Cfrac%7B8r%5E%7B6%7Dt%5E%7B3%7D%20%20%7D%7B4t%5E%7B2%7D%20%7D%29%5E%7B2%7D)
Step-by-step explanation: